Student Reading Interest In Terms Of Learning Motivation, Library Facilities And Library Services, A Case Study At The Universal University Library - Dabur, Feliks; Barek, Florentiana Novita; Harianja, Josepin; Nuraeni, Brigida Endah (LPPJPHKI Universitas Dehasen Bengkulu, 2025)
This study aims to determine the influence of students' reading interest in terms of learning motivation, library facilities and services, both partially and simultaneously, a case study at the Universal University library. This study uses a quantitative research method, the number of respondents is 91 respondents and data collection uses a questionnaire. The results of this study found that the learning motivation variable, t count of 5.642> t table of 1.991 with a significance level of 0.001 <α 0.05. library facility variable t count of 1.010 <t table of 1.991 with a significance level of 0.315> α 0.05 service variable, t count 4.837> t table 1.991 with a significance level of 0.001 <α 0.05. From the f test, it is known that f count 96.320> f table 2.67 with a significance level of 0.001 <α 0.05. This research is limited only to students' reading interest, reviewed from learning motivation, library facilities and services at Universal University Library. This research is useful for researchers and Universal University Library to be used as a reference in making decisions and conducting further research.